Analyzing the dynamic measurement of growth and development in children born after the transplantation of poor quality blastocyst embryos: a propensity matching study - Chunmei Yu; Lijing Bai; Wanchao Zhang; Lin Feng; Xiaoyu Wang; Li Chen; Lingmin Hu (Taylor & Francis Group, 2023)
AbstractObjective This study aimed to observe the dynamic measurement of growth and development in children (0-3 years) after transplantation of low-quality frozen-thawed single blastocysts.Methods This was a retrospective cohort study conducted from January 2016 to December 2019 at a single center. The follow-up data of the children were obtained from the Jiangsu Province Maternal and Child Database. A total of 350 singleton live births were included. Based on the blastocyst score, the live births were divided into good-quality blastocyst embryo (GQE) group (315 live births) and poor-quality blastocyst embryo (PQE) group (35 live births). To improve statistical efficiency and control for potential confounding factors, singletons conceived from PQEs were matched with a 3:1 ratio according to couple ages, BMI, occupation and women AMH levels. Ultimately, 32 children in the PQE group and 95 children (with one missing data) in the GQE group were included in the final analysis.Results After matching for parents' age, BMI, occupation and maternal serum AMH level, there was no significant difference in growth and development of children between the PQE group and GQE group. However, the E2 level on trigger days, the rate of 2PN oocyte, and blastocyst formation rate in the PQE group were significantly lower than in the GQE group (p < .05). The number of embryo transfers (ETs) in the PQE group was higher than in the GQE group (p < .0001). The rate of cesarean section in the PQE group was significantly higher than in the GQE group (p < .05). The height (at 3 months) and head circumference (at 12 months) in the PQE group were lower than in the GQE group (p < .05).Conclusions Transplantation of PQEs did not affect the growth and development of offspring (0-3 years) compared to good-quality blastocysts. However, the oocyte and embryo development potential was lower in the PQE group than in the GQE group. These results provide clinical reference that the transfer of PQE could be acceptable for patients with only PQE embryos.